Control cards as a statistical quality control resource - Drenovac, Aleksandar Živan; Drenovac, Bratislav Živan; Drenovac, Dušan M. (Vojnotehnički glasnik / Military Technical Courier, 2013)
This paper proves that applying of statistical methods can significantly contribute increasing of products and services quality, as well as increasing of institutions rating. Determining of optimal, apropos anticipatory and limitary values, is based on sample`s statistical analyze. Control cards represent very confident instrument, which is simple for use and efficient for control of process, by which process is maintained in set borders. Thus, control cards can be applied in quality control of procesess of weapons and military equipment production, maintenance of technical systems, as well as for seting of standards and increasing of quality level for many other activities.